2009
DOI: 10.1097/cej.0b013e328330eb2f
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality by colorectal cancer in Spain during 1951–2006 and its relationship with behavioural factors

Abstract: Incidence of colorectal cancer has steadily increased in both the sexes and across all age groups during the last decades in Spain, in contrast with other countries where incidence decreased during this period. This increase is more marked among men, probably due to a high exposure to risk factors such as smoking, heavy drinking, overweight and diabetes. Annual age-adjusted mortality rates have increased in Spain during the period 1951-2000, but from that time until 2006 these rates have kept steady in males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
(61 reference statements)
0
10
0
7
Order By: Relevance
“…Several other studies have demonstrated that the disease-free interval between resection of the primary tumour and lung metastasectomy is an independent prognostic factor [2,4,6,12,13]. In a series of 39 patients, Shah et al [14] did not find any statistically significant differences in survival based on whether the appearances of lung and liver metastases were synchronous or metachronous.…”
Section: Time Between Liver and Lung Metastasectomymentioning
confidence: 82%
See 1 more Smart Citation
“…Several other studies have demonstrated that the disease-free interval between resection of the primary tumour and lung metastasectomy is an independent prognostic factor [2,4,6,12,13]. In a series of 39 patients, Shah et al [14] did not find any statistically significant differences in survival based on whether the appearances of lung and liver metastases were synchronous or metachronous.…”
Section: Time Between Liver and Lung Metastasectomymentioning
confidence: 82%
“…Colorectal cancer is the second most common cancer in most European countries [4,5], and the disease recurs after curative surgery in approximately half of patients, with the recurrence most often occurring in the liver or lungs [6,7]. The reported five-year survival rate for colorectal cancer patients with pulmonary metastases who did not undergo surgery is less than 5% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de las mujeres las tasas de CC son inferiores a las de Girona, Murcia y Tarragona y similares a las de País Vasco, Canarias y Navarra y superiores a las de Albacete, Asturias, Cuenca, Granada y Zaragoza; y como en el caso de los hombres las tasas de CR son similares a las más elevadas: País Vasco, Girona, Murcia, Navarra y Tarragona. La tendencia observada fue significativamente ascendente, y más acusada en los hombres, siendo esto compatible con lo observado en nuestro país 5,15 . En países de nuestro entorno se han observado tendencias descendentes mantenidas que se justifican por una mejora en los estilos de vida y en la dieta y la puesta en marcha de actividades de prevención y control, en especial la detección de formas premalignas mediante programas de cribado para detección de sangre oculta en heces y la realización de endoscopias 15,16 .…”
Section: Discussionunclassified
“…La distribución de la incidencia por sexo es acorde con lo esperado, una mayor incidencia en hombres que en mujeres, diferencia que se ha ido incrementando con el paso del tiempo, probablemente por una mayor exposición a estilos de vida menos saludables en el caso de los hombres 15,17 . La razón de tasas entre hombres y mujeres presenta unos valores intermedios en el caso del cáncer de colon, en comparación con los datos suministrados por los registros poblacionales, sin embargo, en el caso del CR presenta los valores más bajos junto con Canarias, Granada y Zaragoza.…”
Section: Discussionunclassified
“…Se ha sugerido que la desigual distribución geográfica del cáncer de esófago puede explicarse por diferencias en la prevalencia de algunos factores de riesgo, entre ellos el consumo de alcohol 98 . Algunos estudios sugieren una correlación entre el nivel de consumo de alcohol y la incidencia de cáncer colorrectal 99,100 . Se observa que los pacientes con abuso/dependencia de alcohol usan otras drogas psicoactivas con cierta frecuencia y tienen otros trastornos de salud mental 101,102 .…”
Section: Intoxicación Etílica Aguda (Iea)unclassified